Physician experience with once-weekly somatrogon versus once-daily rhGH regimen in pediatric patients with growth hormone deficiency: a cross-sectional survey of physicians from the global phase 3 study - Gomez, Roy; Lamoureux, Roger; Turner-Bowker, Diane M.; Loftus, Jane; Maghnie, Mohamad; Miller, Bradley S.; Polak, Michel; Yaworsky, Andrew (Frontiers in Endocrinology, 2023)
Introduction The standard of care for pediatric growth hormone deficiency (pGHD) is once-daily recombinant human growth hormone (rhGH). Somatrogon, a long-acting rhGH, requires less frequent, once-weekly, dosing. We describe physicians’ preference for, experiences, and satisfaction with once-weekly somatrogon vs once-daily rhGH. Methods English-speaking investigators from somatrogon’s global phase III study (NCT02968004) with prior experience using once-daily rhGH were included. Participants answered an online survey containing 14 closed- and open-ended items. Results Twenty-four pediatric endocrinologists (41.7% men; 79.2% practiced at public/private hospitals) from 12 countries with 25.8 ± 12.0 years’ experience treating pGHD completed the survey. In terms of the time and effort required to explain device instructions, injection regimen, procedure for missed injection, and address patients’/caregivers’ concerns, a similar proportion of physicians chose once-weekly somatrogon and once-daily rhGH; 62.5% physicians indicated that once-daily rhGH required greater effort to monitor adherence. Overall, 75% preferred once-weekly somatrogon over once-daily rhGH, 79.2% considered once-weekly somatrogon to be more convenient and less burdensome, and 83.3% were likely to prescribe somatrogon in the future. Overall, 50% felt that once-weekly somatrogon was more beneficial to patients, while 50% chose “No difference”. Most physicians (62.5%) felt both regimens were equally likely to support positive long-term growth outcomes and reduce healthcare utilization. More physicians were “very satisfied” with once-weekly somatrogon (62.5%) than with once-daily rhGH (16.7%). Reduced injection frequency, patient and caregiver burden, increased convenience, and improved adherence were reasons for these choices. Conclusion Physicians had a positive experience with, and perception of, treating pGHD with once-weekly somatrogon.